Early diagnostic value of serum GDF-15, RBP4 and SOCS3 in severe pneumonia with sepsis: Serum GDF-15, RBP4 and SOCS3 in severe pneumonia with sepsis - Wang, Ziyi; Ke, Zhener (Journal of Medical Biochemistry, 2025)
Objective: To explore the early diagnostic value of the serum levels of growth differentiation factor 15 (GDF-15), retinol binding protein 4 (RBP4), and cytokine signal transduction inhibitory factor 3 (SOCS3) in patients with sepsis caused by severe pneumonia (SP).Methods: A total of 110 SP patients admitted to our hospital from December 2023 to February 2025. Based on whether they acquired sepsis, the patients were split into two groups: 52 patients with sepsis and 58 patients without. Additionally, 114 healthy persons of the same age group who passed the health examination test in our hospital during the same period were selected as the control group. The levels of serum GDF-15, RBP4 and SOCS3 were detected via ELISA. Correlation analysis was conducted via the Pearson method. The factors influencing secondary sepsis in SP patients were examined using univariate and multivariate analysis. Serum GDF-15, RBP4, and SOCS3 levels were analyzed for diagnostic effectiveness using a receiver operating characteristic (ROC) curve. The regional differences in the ROC curves of the serum samples were analyzed via the paired comparison method.Results: RBP4 levels were substantially lower (P
Keywords: Severe pneumonia; Sepsis; Growth differentiation factor 15; Retinol binding protein 4; Cytokine signal transduction inhibitor 3; Early diagnosis